Identification of Commands Encoded Optically - Artur ARCIUCH; Tomasz PALYS (Communications of International Proceedings, 2020)
The paper presents the method of simultaneous identification of multiple commands encoded optically. The command encoding algorithm and the multiple command identification algorithm based on Extended Finite State Machine (EFSM) were developed. The method has been examined in a real and virtual environment. The method can be used in systems that implement the control of objects optically by using multiple commands issued by multiple operators.
Keywords: Laser Beam Coding; Augmented Reality; Extended Finite State Machine.